DAMPAK TONTONAN FILM KARTUN TERHADAP PERILAKU SOSIAL ANAK USIA 4-5 TAHUN DI KABUPATEN BONE - Syam, A. Sri Mardiyanti; N, Nurhalisah (EDUCHILD (Journal of Early Childhood Education), 2023)
This thesis discusses the impact of watching cartoon films on the social behavior of children aged 4-5 years in Sipakatau Kindergarten, Tellu Siattinge District. The main problem in this research is how the social behavior of children aged 4-5 years in Sipakatau Kindergarten, Tellu Sittingnge District, Bone Regency is described and what is the impact of watching cartoon films on the social behavior of children aged 4-5 years in Sipakatau Kindergarten, Tellu Sittingnge District, Bone Regency. The type of research used is qualitative with a research approach using a descriptive research approach. This research uses data analysis techniques with the process of reducing data, presenting data, and drawing conclusions. The results of the research show that the picture of children's social behavior is seen when children are able to realize the behavior of working together, helping and forgiving. Apart from that, the positive impact of watching children's social behavior can be seen when the child's attitude is easy to interact with socially, the child is confident so he can easily interact with the social environment, likes to share when he has something, seems to get along and even likes to help his friends who are in trouble, the child has new knowledge, vocabulary. new, and can put it into practice. Meanwhile, the negative impact of cartoon films can be seen in the attitude of children who appear to be indifferent to their surroundings when they are focused on watching cartoon films, having tantrums when their favorites are taken away, and children who will fight with their younger siblings because they are fighting over cellphones to use to watch cartoon films.